212 Development and implementation of research team: Lessons learned from conducting studies focusing on sleep and brain aging. (April 2022) - Moon, Chooza; Hoth, Karin
Abstract : OBJECTIVES/GOALS: This poster summarizes the development and implementation of research exploring the relationship between sleep and brain health. METHODS/STUDY POPULATION: Three pilot studies and two secondary data analyses were conducted on 20 older adults with coronary artery disease and 30 older adults without major cardiovascular disease. They were recruited for 10 older adults with multiple chronic conditions. The study included interviews, magnetic resonance imaging, and sleep assessment of participants. Data were also gathered from two secondary sources on multiple chronic conditions, sleep, neuroimaging, cognition, and Alzheimers biomarkers. RESULTS/ANTICIPATED RESULTS: The multidisciplinary team was from nursing, medicine, cardiology, psychology, neuroscience, radiology, and data science to address the separate research aims. The pilot studies and secondary data analyses were successfully implemented. The University of Iowa Institute for Clinical and Translational Science, Center for Advancing Multimorbidity Science, and Iowa Neuroscience Consortium supported the collaboration. The teams have found that sleep and circadian rhythms characteristics may be associated with not only coronary artery disease, but also multiple chronic conditions. Having sleep disorders and reduced circadian amplitude can be associated with white matter microstructure and functional connectivity. These collaborations provided multiple funding and publication opportunities. DISCUSSION/SIGNIFICANCE: Interdisciplinary team research is important to enhance translational science. Although challenges were identified, using multiple methods and dataset sources with multidisciplinary team members enabled opportunities to explore multifaced topics related to sleep and brain aging.